The Evaluation of Indonesian Labour Market in Optimizing Demographic Dividend in 2016 - Siectio Dicko Pratama; Rizal Rahadiana (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2018)
Considering the structure of its population, Indonesia has the potential to enjoy advantages that are associated with a demographic dividend in the not too distant future. Nonetheless, there are challenges the country is facing, one of which is the coming into being of the ASEAN Economic Community (AEC). This research describes the state of the labor market in Indonesia to identify how best it can benefit from the demographic dividend, including problems, and how to resolve them. The research uses Multiple Linear Regression with backward elimination method. Re-sults of the research indicated that independent variables in the model showed a negative and significant influence on the economy. To that end, working below 15 hours, and unemployment of the educated are the two most important problems facing in Indonesian labor market. Rec-ommended solutions to the problem is to encourage educated unemployed to participate in Mi-cro and Small Manufactures that deal in processing agricultural commodities to become ready-to-consumer goods.